2005
DOI: 10.1002/art.21331
|View full text |Cite
|
Sign up to set email alerts
|

Muscle metabolites, detected in urine by proton spectroscopy, correlate with disease damage in juvenile idiopathic inflammatory myopathies

Abstract: Objective. To assess for novel markers of muscle damage using urinary muscle metabolites by 1 H magnetic resonance spectroscopy in patients with juvenile idiopathic inflammatory myopathy (IIM). Methods. Creatine (Cr), choline (Cho), betaine (Bet), glycine (Gly), trimethylamine oxide (TMAO), and several other metabolites were measured in first morning void urine samples from 45 patients with juvenile IIM and from 35 healthy age-matched controls, and correlated with measures of myositis disease activity and dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…The creatinine depletion observed in urine from the animal models and T2DM patients may have arisen because of a variety of reasons such as changes in muscle mass, creatinine reabsorption, cell leakage, and changes in caloric intake. However, a decline in the renal glomerular filtration rate (GFR) associated with diabetic nephropathy (8,29,39) would not only explain this observation but also a variety of other metabolite changes. For example, reduced urinary allantoin excretion is also indicative of reduced GFR as allantoin is not reabsorbed across the proximal tubule, and thus its urinary concentration is thought to accurately reflect glomerular filtration (5,19).…”
Section: Discussionmentioning
confidence: 99%
“…The creatinine depletion observed in urine from the animal models and T2DM patients may have arisen because of a variety of reasons such as changes in muscle mass, creatinine reabsorption, cell leakage, and changes in caloric intake. However, a decline in the renal glomerular filtration rate (GFR) associated with diabetic nephropathy (8,29,39) would not only explain this observation but also a variety of other metabolite changes. For example, reduced urinary allantoin excretion is also indicative of reduced GFR as allantoin is not reabsorbed across the proximal tubule, and thus its urinary concentration is thought to accurately reflect glomerular filtration (5,19).…”
Section: Discussionmentioning
confidence: 99%
“…Due to limitations in laboratory resources most studies have tested samples from 10-30 patients, with a control or normal group of at least similar size. This limitation in the number of samples is compounded in human studies where subject compliance may be poor (Chung et al 2005). Although reference to Geigy scientific tables is common, the information is based upon limited research with similarly small sample sizes (Geigy 1981(Geigy -1992.…”
Section: Introductionmentioning
confidence: 99%
“…Bilgic et al [38•] recently showed a significant correlation between a type I interferon signature and disease activity in adults and children with IIM. Additionally, the ratio between urine creatine and creatinine has been shown to correlate with disease damage [39]. There is considerable optimism that one of these markers (or another related one) will become a useful assessment in children with JIIM in the future.…”
Section: Laboratory Assessmentmentioning
confidence: 99%